NURSE EMPOWERMENT THROUGH ENTREPRENEURIAL INNOVATION AND ORGANIZATIONAL CHANGE: A SYSTEMATIC REVIEW OF LEADERSHIP STRATEGIES IN NURSING ROLE EXPANSION - Tasnidar Tasnidar; Yunia Wardi; Susi Evanita; Hendrik Heri Sandi; Syamsul Amar; Vidyarini Dwita (RADJA PUBLIKA, 2025)
Nurse empowerment is an important strategy in facing the challenges of an increasingly complex and competitive health care system. This study aims to systematically review how entrepreneurial innovation and organizational change supported by transformational leadership can expand the role of nurses and enhance their strategic contribution to the health system. A literature search was conducted on the Scopus database for studies published in the last ten years, namely from January 1, 2015 to December 31, 2024. Eight articles that met the inclusion criteria were analyzed thematically and narratively. The results of the review indicate that the integration of entrepreneurship into nursing practice encourages the formation of new service models such as independent practice, home care and telenursing that are more responsive to patient needs. Flexible organizational structures, collaborative work cultures and performance-based incentive systems strengthen the role of nurses as agents of change. Participatory leadership has been shown to create a work climate that supports innovation and initiative taking at the clinical level. Challenges such as limited infrastructure, training gaps, and cultural and structural barriers still need to be overcome to optimize nurse empowerment as a whole. This study concludes that empowering nurses through entrepreneurial innovation and organizational change requires a multidimensional approach and sustainable policy support so that nurses can play a strategic role in building a resilient health system that is oriented towards future needs.